Acoustic characteristics of optimum voice - Sreedevi H.S (Journal of All India Institute of Speech and Hearing, 1970)
The present study was conducted to determine the acoustical aspects of optimum voice. 100 subjects (50 males and 50 females) were selected for the study in the age range of 17-50 years.